1993
DOI: 10.1145/159764.159762
|View full text |Cite
|
Sign up to set email alerts
|

Integration of interpersonal space and shared workspace

Abstract: This paper describes the evolution of a novel shared drawing medium that permits co-workers in two different locations to draw with color markers or with electronic pens and software tools while maintaining direct eye contact and the ability to employ natural gestures.We describe the evolution from ClearBoard-1 (based on a video drawing technique) to ClearBoard-2 (which incorporates TeamPain~a multi-user paint cdtor).Initial observations based on use and experimentation are reported. Further experiments are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(126 citation statements)
references
References 15 publications
4
119
0
3
Order By: Relevance
“…Telepresence [15] can be characterised by the feeling of "being there", achieved primarily by establishing audio and video channels between distant locations [14]. Users are provided with stimulation to their senses giving them the feeling or appearance that they are present at a different location other than their true current location.…”
Section: Related Workmentioning
confidence: 99%
“…Telepresence [15] can be characterised by the feeling of "being there", achieved primarily by establishing audio and video channels between distant locations [14]. Users are provided with stimulation to their senses giving them the feeling or appearance that they are present at a different location other than their true current location.…”
Section: Related Workmentioning
confidence: 99%
“…Many studies have examined the collaboration styles used by adults when sharing an artifact such as a sketchpad (Tatar et al 1991, Minneman & Bly 1991, Ishii, Kobayashi & Grudin 1992, Greenberg, Hayne & Rada 1995. We wanted to see whether childrens' collaboration styles were similar to those of adults, and to see whether they encountered any unforeseen problems when interacting through TurboTurtle as a shared artifact.…”
Section: Preliminary Evaluationmentioning
confidence: 99%
“…This gives the possibility to simultaneously display the remote partner as well as data shared between the two connected stations. This application scenario is similar to the ClearBoard metaphor 'talking through and drawing on a big transparent glass window' introduced by Ishii, Kobayashi, et al [2] [5].…”
Section: 1mentioning
confidence: 99%
“…Ishii, Kobayashi, et al [5] suggested that even more important than eye contact may be the more general capability called gaze awareness: The ability to monitor the direction of a partner's gaze and thus his or her focus of attention. Eye contact can be seen as a special case of gaze awareness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation